Computational Integrative Physiology: At the Convergence of the Life and Computational Sciences - Siregar, P.; Julen, N.; Sinteff, J.-P. (Methods of Information in Medicine, 2003)
Objective: In this paper we outline how Computational Integrative Physiology (CIP) can help unravel the mechanisms of normal and pathological biological processes. Our objective is to illustrate how CIP is firmly grounded on the life and computational sciences.Method: After describing a general theoretical framework for CIP, we will center our discussion on cardiac rhythmic disorders with a particular focus on the Long QT syndrome that will serve as a case example. Within this context, we will describe multi-scale processes in biological, medical and in general mathematical terms, starting from the control of gene expression to the electrical activity of the entire heart. We will therefore proceed from the smaller microscopic scales to the larger macroscopic ones. In doing so, we will illustrate, at least in a qualitative sense, how CIP can be accomplished by showing some of the relations that can exist between mathematical variables characterizing models of different space-scales.Conclusion: We will conclude by putting forth how CIP and the related fields of bioinformatics and medical informatics are necessary to derive meaningful knowledge from the huge and exponentially growing biological and medical data.
Keywords: Computational biology; integrative physiology; cardiology; multiscale modeling; biomathematics